Synthesis and Redox Chemistry of a Homoleptic Iron Arsenic Prismane Cluster. Issue 17 (11th April 2022) - Riesinger, Christoph; Dütsch, Luis; Scheer, Manfred
Abstract: The redox chemistry of the homoleptic iron prismane cluster [Cp*Fe3 (μ3, η 4:4:4 ‐As6 )] (A, Cp*=C5 Me5 ) is investigated both electrochemically and synthetically. While its first oxidation leads to the diamagnetic species [Cp*Fe3 (μ3, η 4:4:4 ‐As6 )][X] ([1][TEF], [1][FAl], [TEF] − =[AlOC(CF3 )3 4 ] −, [FAl] − =[FAlO(1‐C6 F5 )C6 F10 3 ] − ), the second oxidation yields the paramagnetic [Cp*Fe3 (μ3, η 4:4:4 ‐As6 )][TEF]2 ([2][TEF]2 ). The reduction of A leads to the monoanionic compound [K@[2.2.2]‐cryptand][Cp*Fe3 (μ3, η 4:4:4 ‐As6 )] ([K@crypt][3] ), while a second reduction could only be traced spectroscopically. All compounds were comprehensively characterized, revealing the structural changes accompanying the described redox processes. All findings are supported by spectroscopic as well as computational studies. Abstract : The redox chemistry of the newly synthesized homoleptic iron arsenic prismane cluster [Cp*Fe3 (μ3, η 4:4:4 ‐As6 )] (A ) is investigated. While oxidation leads to an extended distortion of the prismane geometry by cleavage of one of the As−As bonds, reduction leads to a symmetrization of the cluster.